The Effect of Gross Regional Domestic Product (GRDP), Investment, Population, and Inflation on Regional Original Revenue (PAD) of Nusa Tenggara Barat Province (NTB) in 2010-2022 - Ni Nengah Winda Naraswari; Abdul Manan; Eka Agustiani (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This research examines the influence of GRDP, Investment, Population and Inflation on the Original Regional Income of NTB Province for 2010-2022. The research was conducted with the aim of analyzing whether there is a partial or simultaneous influence between GRDP, Investment, Population and Inflation on the Original Regional Income of NTB Province for 2010-2022. The results of this research show that partially GRDP has a positive and significant effect on the Original Regional Income of NTB Province with a Prob. (Significance) value of 0.0221 (<0.05), Investment has a positive and significant effect on Original Regional Income of NTB Province with a Prob. (Sig.) of 0.0011 (<0.05), Population has a positive and significant effect on the Original Regional Income of NTB Province with a value of Prob. (Sig.) is 0.0144 (<0.05), and inflation has a positive and insignificant effect on the NTB Province's Original Regional Income with a value of Prob. (Sig.) of 0.8639 (>0.05). Simultaneously GRDP, Investment, Population and Inflation have a positive and significant effect on the Original Regional Income of NTB Province with a value of Prob. (Sign.) of 0.000001 (<0.05).